Wired together: collaborative problem-based language learning in an online forum. - Abdullah, Mardziah Hayati; Tan, Bee Hoon (2008)
A descriptive study was conducted on the use of a collaborative Problem-Based Learning activity in an undergraduate ESL course on language and Information Technology in a Malaysian university. An asynchronous online conferencing forum was set up as the medium of interaction for the students to engage in the activity over a period of three weeks. The findings show that the PBL activity offered both linguistic and affective benefits in the ESL class. It stimulated communication and generated substantial discussion on a variety of topics, resulting in the use of English for academic and social interaction. It raised the students’ awareness of a real audience for the language task they were working on and provided a meaningful context within which language learning, including the exploration of grammatical rules, took place. The PBL activity also promoted self-directed learning and a sense of ownership of the learning activities which are important to the development of learner autonomy. The online domain was found to enhance both the PBL process itself and the benefits it offered to language learning. The accessibility and asynchronicity of the forum encouraged and eased interaction, and provided a space for the maintenance of group spirit and participation of more timid students. The challenges faced by ESL teachers in using such a PBL approach include the need to be facilitators more than instructors, and to ensure that the interaction among the students is in English.